DIVERSITY AND ABUNDANCE OF NEMATODES IN GUAVA (Psidium guajava L.) CULTIVATION IN LAMPUNG - Nabilah, Nabilah; Swibawa, I Gede; Suharjo, Radix; Fitriana, Yuyun (Universitas Lampung, 2021)
Diversity and abundance of nematodes in guava (Psidium guajava L.) cultivation in Lampung. Crystal guava agroecosystem is inhabited by many species of plant parasitic nematodes. However, information regarding this topic was still limited. This study aimed to understand the species dominancy of nematodes in crystal guava cultivation in Lampung. Sampling was carried out in three locations of guava crystal plantations: Lampung Timur, Lampung Tengah, and Tanggamus. The laboratory analysis was done at the Plant Pest Science Laboratory and Agricultural Biotechnology Laboratory, Universitas Lampung. The study was conducted in December 2019 – July 2020. Nematodes were identified to the level of the genus. The Prominance value (PV) was used to assess the nematodes genus dominancy. The results showed that the nematodes inhabiting the crystal guava agro-ecosystem in Lampung was both plant parasitic and free-living nematodes. The plant parasitic nematodes were identified as Meloidogyne, Aphelenchus, Hemicriconemoides, Tylenchus, Aphelenchoides, and Xiphinema, while free-living nematodes was Rhabditis, Dorylaimine, Dorylaimus, and Mononchus. The dominant plant parasitic nematode was Meloidogyne and the dominant free-living nematode was Rhabditis. The abundance of Meloidogyne /300 mL of soil was 351.47 individuals in Lampung Timur, 124.27 individuals in Lampung Tengah, and 82.18 individuals in Tanggamus. The dominant free-living nematode in the three locations was Rhabditis.